2006
DOI: 10.1038/modpathol.3800529
|View full text |Cite
|
Sign up to set email alerts
|

pT classification, grade, and vascular invasion as prognostic indicators in urothelial carcinoma of the upper urinary tract

Abstract: Clinicopathologic features predictive of patient outcome in upper urinary tract urothelial carcinoma are not well defined. The aim of this study was to assess the role of pT classification, tumor grade, and vascular invasion in predicting metastasis-free survival. A total of 190 consecutive invasive upper urinary tract urothelial cancers operated between 01/1984 and 12/2004 were re-evaluated with respect to pT classification, tumor grade (according to the three-tiered WHO 1973 and the recent two-tiered grading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
27
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 33 publications
6
27
1
5
Order By: Relevance
“…Although several studies have identified LVI as a poor prognostic feature, only a few have controlled for possible confounding factors by using multivariate analyses. 4,8,12,23,24 In agreement with several single-center reports, our multiinstitutional study revealed that 25% of patients undergoing RNU for UTUC had histologically identifiable LVI. As previously reported in several cystectomy and RNU series, LVI was associated with advanced stage, grade, and LN status.…”
Section: 46supporting
confidence: 76%
See 4 more Smart Citations
“…Although several studies have identified LVI as a poor prognostic feature, only a few have controlled for possible confounding factors by using multivariate analyses. 4,8,12,23,24 In agreement with several single-center reports, our multiinstitutional study revealed that 25% of patients undergoing RNU for UTUC had histologically identifiable LVI. As previously reported in several cystectomy and RNU series, LVI was associated with advanced stage, grade, and LN status.…”
Section: 46supporting
confidence: 76%
“…4,20,21 Unlike previous reports, however, we provide compelling data that the new 2-tiered tumor grading system is a powerful independent predictor of recurrence and death from UTUC. Largely depending on the stage of the primary tumor, 20-40 % of patients with UTUC are historically found to harbor LN metastases.…”
Section: 46contrasting
confidence: 45%
See 3 more Smart Citations